Secular Changes in Youth Labour Markets and Youth Unemployment in Canada - Weiermair, Klaus (Relations industrielles / Industrial Relations, 1986)
This paper considers the evolution of Canadian youth unemployment and associated patterns of behavior in youth labor markets from a long run perspective